Strategi Komunikasi Seorang Dosen Dalam Menciptakan Suasana Pembelajaran Yang Menarik Di Prodi Komunikasi Universitas Sari Mutiara - Mega Ulva Sari Sihombing; Evi Enitari Napitupulu; Nurhawati Simamora; Joses Setiawan Loi (Universitas Sari Mutiara Indonesia, 2024)
This study aims to analyze the Communication Strategy of a Lecturer in overcoming learning boredom of Communication Science students. The study emphasizes a qualitative approach, involving 2 lecturers, one lecturer as an observer and one lecturer acting as a direct participant, while the number of students is 45 people in class A. The results of the study indicate that in overcoming learning boredom, lecturers develop an active Communication Strategy of a Lecturer, but still prioritize assertiveness, take full social initiative so that students can imitate, are able to integrate with their social environment, are able to express their opinions emotionally but in a controlled manner, send information with full attention, give orders but show assertiveness, and attention. In addition, lecturers have an imperfect Emotive style Communication Strategy of a Lecturer, an less established Director style, a Reflective style, and have a cautious supportive style. The Communication Strategy of a Lecturer in learning will have an impact on the actualization and implementation of their social life.